Factors supporting user interface design of mobile government application - Pinnaree Kureerung (2019)
© 2019 Association for Computing Machinery. M-Government services are an extension of e-Government. M-Government services, are an extension to e-Government services, in which citizens receive information and services through their mobile devices anywhere and anytime. Although m-government applications share similar characteristics with other mobile applications, there are unique characteristics to be considered when designing the user interface. User interface design guidelines that are applicable to general mobile applications are not always suitable to be used with m-government applications. An appropriate usability engineering framework for m-government application is needed. It should cover the unique characteristics and, ultimately, lead to satisfaction of diverse citizens. Therefore, this paper focuses on developing a usability engineering guideline for designing user interface of m-government application. The pilot study was performed using Delphi study, clustering, and classification methods to discover factors affecting the design of user interface. As a result, eleven factors were found to be crucial to the user interface design. The factors identified from experts and users includes learnability, Privacy, Simplicity, Governance, Organization, Effectiveness, Security, Responsiveness, Simultaneousness, Memorability, and Notification.. The factors were then analyzed to form a usability engineering guideline that will guide developers in designing the user interface with desired characteristics.